Modified Maximum Power Point Tracking on Models of a 400 Wp Wind Power Plant - Dwiana Hendrawati; Mulyono Mulyono; Wahyono Wahyono; Suwarti Suwarti; Nur Fatowil Aulia; Ariyanto Ariyanto; Brainvendra Widi Dinova (Politeknik Negeri Semarang, 2022)
Many papers discuss the Maximum Power Point Tracking (MPPT) control simulation